2018
DOI: 10.1186/s13567-018-0589-8
|View full text |Cite
|
Sign up to set email alerts
|

The Riemerella anatipestifer M949_RS01035 gene is involved in bacterial lipopolysaccharide biosynthesis

Abstract: In this study, the Riemerella anatipestifer mutant strain RA1062 was obtained by screening a random Tn4351 transposon mutant library. The mutant strain was unreactive with the anti-CH3 lipopolysaccharide monoclonal antibody, as demonstrated with an enzyme-linked immunosorbent assay, and its M949_RS01035 gene was inactivated. When cultured in trypticase soy broth, the late stage growth of the mutant RA1062 was significantly decreased. The mutant RA1062 was stained with crystal violet and presented a rough lipop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…Similarly, Zou et al mutated the M949_1603 gene in the above gene cluster in R. anatipestifer CH-3 and found that the LPS of the mutant strain lacks the O-antigen chain(Zou et al, 2015). Two other studies reported similar results, that is, the expression of M949_RS07580 was significantly downregulated in the CH-3 mutant strain, which lacks O-antigen repeat units(Dou et al, 2017; Dou et al, 2018). M949_RS07580 is also located in the O-antigen gene cluster.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, Zou et al mutated the M949_1603 gene in the above gene cluster in R. anatipestifer CH-3 and found that the LPS of the mutant strain lacks the O-antigen chain(Zou et al, 2015). Two other studies reported similar results, that is, the expression of M949_RS07580 was significantly downregulated in the CH-3 mutant strain, which lacks O-antigen repeat units(Dou et al, 2017; Dou et al, 2018). M949_RS07580 is also located in the O-antigen gene cluster.…”
Section: Discussionsupporting
confidence: 55%
“…The LD 50 of CZG-1 was 35.122 CFU/ml. In Dou et al results about R. anatipestifer , the LD 50 of serotype 1 CH3 strain was 7.50 × 10 7 CFU/ml ( 30 ). Another serotype 1 R. anatipestifer YL4 strain has an LD 50 of about 4.74 × 10 6 CFU/ml ( 31 ).…”
Section: Discussionmentioning
confidence: 95%
“…After immunization of young ducks using drinking water, aerosol, or subcutaneous inoculation, analysis of serum titers using ELISA demonstrated that the attenuated vaccine induced high levels of immune antibodies that persisted for a long time compared to inoculation with the inactivated vaccine. Lymphocyte transfer tests also indicated that the attenuated vaccine induced a strong cellular immune response ( Dou et al, 2018 ). Compared with the above study, The R. anatipestifer YMΔ phoP strain was constructed by homologous recombination, which mainly has a protective effect on ducks infected with serotype 1.…”
Section: Discussionmentioning
confidence: 99%